Genetic and molecular analysis of the anthocyanin pigmentation pathway in Epimedium - Mi, Yaolei; He, Ruikun; Wan, Huihua; Meng, Xiangxiao; Liu, Di; Huang, Wenjun; Zhang, Yanjun; Yousaf, Zubaida; Huang, Hongwen; Chen, Shilin; Wang, Ying; Sun, Wei (Frontiers in Plant Science, 2023)
Flower color is an ideal trait for studying the molecular basis for phenotypic variations in natural populations of species. Epimedium (Berberidaceae) species exhibit a wide range of flower colors resulting from varied accumulation of anthocyanins and other pigments in their spur-like petals and petaloid sepals. In this work, the anthocyanidins of eight different Epimedium species with different floral pigmentation phenotypes were analyzed using HPLC. Twelve genes involved in anthocyanin biosynthesis were cloned and sequenced, and their expression was quantified. The expression levels of the catalytic enzyme genes DFR and ANS were significantly decreased in four species showing loss of floral pigmentation. Complementation of EsF3’H and EsDFR in corresponding Arabidopsis mutants together with overexpression of EsF3’5’H in wild type Arabidopsis analysis revealed that these genes were functional at the protein level, based on accumulation of anthocyanin pigments. These results strongly suggest that transcriptional regulatory changes determine loss of anthocyanins to be convergent in floral tissue of Epimedium species.